2003年夏季东南印度洋上层海洋的水文特征 - 贺志刚; 董兆乾; 胡建宇 (2003)
本文利用 2 0 0 3年 2月我国第 1 9次南极考察队在南极普里兹湾到澳大利亚弗里曼特尔南印度洋断面上获得的XBT和XCTD数据 ,分析了该断面上层的水团分布和锋面的特征 ,并讨论了极锋以南表层的淡水输入和热量输入与海冰、降水及平流之间的关系。南极夏季表层水(AASSW)、亚南极表层水 (SASW)、亚热带表层水 (STSW)分布于温盐跃层之上的混合层中 ,由南向北依次分布。AASSW之下是向北延伸的温度最小值层 ,即冬季水 (WW) ,其下则是涌升的上层南极饶及深层水 (UCDW)。南侵的高温高盐的亚热带表层水 (STSW)之下是温度和盐度相对均匀的亚南极模式水 (SAMW)。本航次发现 ,在 63.5°S ,79.7°E的 60 0m以深有低盐水体 (相对其周围水体 )存在 ,核心盐度 34.5 8,位于 80 0— 90 0m水深之间。这是历次考察在该断面所不曾观测到的现象。断面上的锋面从南向北依次为南极陆坡锋 (ASF)、极锋 (PF)、亚南极锋 (SAF)和亚热带锋 (STF)。ASF位于 65°S以南的 1 0 0m以深 ,等温线和等盐线向南倾斜 ;PF位于 5 4°S ,90 .4°E ;SAF位于 45 .3°— 47.5°S ,1 0 2 .5°— 1 0 4 .4°E之间 ,深达整个测量深度 ,温度具有两个高梯度核心 ;首次在该断面观测到双STF结构 ,位于 41 .9°— 42 .6°S,1 0 6.7°— 1 0 7.3°E和 37.7°— 38 The data of 28 XBTs and 25 XCTDs obtained by the 19 th Chinese National Antarctic Research Expedition in the section from Prydz Bay, Antarctica to Frementle, Australia in February, 2003 are used to analyze the properties of water masses distribution and fronts of the upper ocean, and the influence of sea ice, precipitation and advection on the freshwater and heat input of sea surface south of Polar Front (PF) is discussed. An unusual low salinity (34.58) water mass is observed at the depth of 800—900m in the location around 63.5°S,79.7°E. The Antarctic Slope Front (ASF), Polar Front (PF), Subantarctic Front (SAF) and Subtropical Front (STF) appear in the investigation section from south to north. PF lies on 54°S, ,90.4°E; SAF locates at 45.3°—47.5°S ,102.5°—104.4°E and reaches the bottom of the measured depth with two high temperature gradient cores; For the first time double STF structures is discovered and locate at 41.9°—42.6°S, ,106.7°—107.3°E and 37.7°—38.9°S, 109.8°—110.7°E, respectively. PF, SAF and STF can be identified from the properties of surface layer in some degree. Especially, the representation of SAF in the temperature and salinity of surface layer is distinct. The flow cores of ACC passing the investigation section locate at PF and SAF, which is in consistent with the historical data. The variation trend of freshwater and heat input on the sea surface south of PF is in close correlation with the meridional distribution of the thickness of sea ice and the range of sea ice extending northward in this region in austral winter. 国家自然科学基金重点项目 (4 983 60 1 0和 40 2 3 1 0 1 3 );; 国家科技部公益项目(2 0 0 1DIA5 0 0 40 );; 基础性专项“南极地区地球环境监测与关键过程研究”资助